High Thermoelectric Performance of Metallophthalocyanine Molecular Junctions with cis and trans Configuration (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
A theoretical comparative study of electrical and thermoelectric properties of metallophthalocyanine (MPc) molecule sandwiched between two gold leads have been studied. Metallophthalocyanine (MPc) with different transition metal ions at the center of phthalocyanine (Fe, Co, and Cu) have been investigated in two different molecular configurations, cis and trans. The results show that the electrical conductance and thermopower are changed by varying the transition metal-center and both of them show higher values around Fermi energy in trans configuration than cis one. Higher value of figure of merit ZT has been computed in Fe-Pc in cis configuration ~ 3.3. High (ZT) values demonstrated that these molecular junctions are efficient thermoelectric applications